Total production costs of construction enterprise features of distribution - Husarova, L.; Rubtsova, O.; Olenich, D.S. (Ways to Improve Construction Efficiency, 2021)
The article considers the peculiarities of the distribution of total production costs, taking into account the specifics of the construction enterprises of Ukraine. It is established that the accounting processes are regulated by UAS 16 "Costs" and UAS 18 "Construction contracts", but in practice the implementation of the distribution of overhead costs becomes a formal procedure due to insufficient definition and presentation in the current regulatory framework of the classification of costs. It is noted that in construction there are three types of cost of construction and installation work: estimated, which includes regulatory costs due to estimated norms and current prices; planned, which includes the cost of construction and installation work and is determined on the basis of technical and economic calculations using economically justified norms and standards of costs for construction and installation work under normal capacity of the construction company and the actual, including the actual costs of the construction company, incurred during construction and installation work. This feature leads to the possibility of significant differences in the actual and estimated cost of construction. The schematic connection of the classification of costs by economic elements and costing items in calculating the cost of construction and installation work is given. It is determined that the improvement of accounting for total production costs should be an element of strategic management in the construction company as there is a tendency to increase in recent years. Carrying out the correct distribution of total production costs requires further development of regulatory and methodological framework, firstly, by improving the classification of indirect costs with the development of criteria for determining their fixed and variable part, and secondly, developing criteria for selecting the optimal distribution base of construction enterprises. It is considered promising to use information technology for more accurate calculations and improve the working conditions of analysts in the distribution of total production costs.